ISOLASI DAN IDENTIFIKASI SENYAWA FLAVONOID DARI DAUN TUMBUHAN KEREHAU (Callicarpa longifolia Lam.) - Subur P Pasaribu; Erwin -; Putri Istiyanti (JURNAL KIMIA MULAWARMAN, 2014)
The flavonoid had been isolated from ethyl acetate extract of Kerehau leaf (Callicarpa longifolia Lam.). Extraction was done by maceration and fraction method. Isolation of pure compound was done by chromatographic flash coloumn. The resulted of isolated flavonoid was yellow greeness powder and 174-178°C melting point. Based on data IR can be conclude that isolated compound is flavonol group. Effect of toxicity from isolate identified with presentage of prawn larva (BSLT method) and counted by probit analysis (LC 50 ). The results of this test showed that the the isolate was very toxic with LC 50 value of 26,8824 ppm. Keywords: Kerehau (Callicarpa longifolia Lam.), Isolation, Flavonoid, BSLT